Cash waqaf and Islamic microfinance - untapped economic opportunities - Md Saad, Norma; Anuar, Azizah (Institute of Advanced Islamic Studies, 2009)
The success of microfinance programs in alleviating poverty in many countries has spurred the development of faith-based microfinance institutions. Muslims have combined certain elements in Islamic finance and microfinance to create a new program called Islamic microfinance and use it as a tool to fight poverty in their community. Even though microfinance is proven successful in fighting poverty, current microfinance practiced by commercial banks in Malaysia has several shortcomings. Among other things, the weaknesses are stringent credit evaluation and missing the real target group, i.e., the poor and the needy. Furthermore, the mode of financing is mostly personal loan using bai-al inah, whereby the use of the loan is to fulfill personal consumption instead of income generating activities. Given these shortcomings, the paper explores the possibility of using cash waqaf as a new source of fund for Islamic microfinance and proposes new concept and application of Islamic microfinance so that it is truly in line with the Islamic spirit of microfinance. It is hoped that with this new concept and application of Islamic microfinance, the use of microfinance is genuinely to cater for the needs of the poor and the needy and as a means to combat poverty as well as generating socio-economic growth of the Muslim Ummah.